CHARACTERISTICS OF RICE HUSKS AND SILICA CONTENT FROM SEVERAL SUPERIOR VARIETIES IN WEST SUMATRA - Anwar Kasim; Emriadi; Nalwida Rozen; Ruri Wijayanti (LLDIKTI X Sumbar, Riau, Jambi, Kepri, 2024)
The processing of rice husk to obtain silica ash has been carried out and then from the results of the silica preparation, the actual silica content was determined. The purpose of this study is to determine the varieties that contain the highest silica from the existing superior varieties. The research method carried out is the experimental method. Sampling of rice husks from six superior rice varieties in West Sumatra was taken from several areas in Regency / City West Sumatra which has superior rice varieties. There are three stages carried out in this study. The first stage was the preparation of the husk for analysis by giving preliminary treatment, the second stage was processing the husk into silica ash and the third stage was determining the silica content of silica ash. The results showed that the superior rice variety with the highest silica content was the IR-42 variety at 95.759%, and the lowest silica content was the Junjuang variety at 93.27%. Meanwhile, based on the silica ash yield obtained, the superior rice variety that has the highest silica ash yield is the Bujang marantau variety which is 8.3%, while the lowest yield is found in the anak daro variety which is 5.5%. Then the variety that has the lowest specific surface area of silica ash is the junjuang variety and the highest is the Kuriak Kusuik variety which is 258.499 m2 /g. Keywords: Rice husk; silica; West Sumatra; high yielding varieties.